2019
DOI: 10.1021/acs.jpclett.8b03697
|View full text |Cite
|
Sign up to set email alerts
|

Doping of Monolayer Transition-Metal Dichalcogenides via Physisorption of Aromatic Solvent Molecules

Abstract: Two-dimensional (2D) transition metal dichalcogenides (TMDs) recently emerged as novel materials displaying a wide variety of physico-chemical properties that render them unique scaffolds for high-performance (opto)electronics. The controlled physisorption of molecules on the TMD surface is a viable approach to tune their optical and electronic properties. Solvents, made of small aromatic molecules, are frequently employed for the cleaning of the 2D materials or as "dispersant" for their chemical functionaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 38 publications
3
69
0
Order By: Relevance
“…22 The effects of organic molecules adsorption such as TCNQ, TCNE, TTF, BV, F4TCNQ, and benzene on the electronic and optical properties of the monolayer MoS 2 have been studied in the literature. [23][24][25][26] A reduction of the bandgap was found due to the existence of the at molecular levels of the organic molecules in the bandgap region of the monolayer MoS 2 . The theoretical study showed that the adsorption of TCNQ signicantly enhances the peak height of the optical absorption of the monolayer MoS 2 in the infrared region of the spectrum.…”
Section: Introductionmentioning
confidence: 98%
“…22 The effects of organic molecules adsorption such as TCNQ, TCNE, TTF, BV, F4TCNQ, and benzene on the electronic and optical properties of the monolayer MoS 2 have been studied in the literature. [23][24][25][26] A reduction of the bandgap was found due to the existence of the at molecular levels of the organic molecules in the bandgap region of the monolayer MoS 2 . The theoretical study showed that the adsorption of TCNQ signicantly enhances the peak height of the optical absorption of the monolayer MoS 2 in the infrared region of the spectrum.…”
Section: Introductionmentioning
confidence: 98%
“…Various methods have been proposed for tuning E F within the band gap of TMDCs, including substitution with dopant atoms 15 , stacking with other 2D materials 16 , exposure to gases [6][7][8]17 , adsorption of alkali metals 18,19 , and adsorption of organic molecules [20][21][22][23][24][25][26] . In accordance with this approach, deposition of molecular electron acceptors or donors on TMDCs has been suggested as a very effective strategy for controlling the E F position via doping, and accordingly high-performance TFTs were realized 22,24,26 .…”
mentioning
confidence: 99%
“…Solvent molecules are known to determine dielectric screening and doping when physisorbed on the surface of 2D semiconducting materials 7b,9. To explore the effects of solvents on BP, FETs were fabricated by E‐beam lithography by using mechanically exfoliated BP flakes as prototypical electroactive material.…”
Section: Resultsmentioning
confidence: 99%
“…To further characterize solvent effects on BP FETs, we explored the change in optical properties of BP upon solvent physisorption. Unlike TMDs whose photoluminescence (PL) spectra could reflect the level of doping by solvent molecules via the quantification of the exciton and trion intensity, photoluminescence of black phosphorus has barely been studied due to their small bandgap in few‐layer materials and high exciton anisotropy 2c,9,16. The complex behavior of excitons and trions made it difficult to quantify the charge density modulation by physisorbed molecules, as shown in Figure S6 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%